Comparative demography of the exotic Harmonia axyridis with other aphidophagous coccinellids reared on artificial diet - Milléo, Julianne; Fernandes, Francisco Sales; Godoy, Wesley Augusto Conde (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to compare biological aspects and life table parameters of the coccinellids Harmonia axyridis, Cycloneda sanguinea and Hippodamia convergens. Insects were fed eggs of Anagasta kuehniella, and reared at 24.5±1ºC, 70±10% relative humidity, with a 12‑hour photophase. Hippodamia convergens took about 1.6‑day to complete development, longer than H. axyridis, and 2.4‑day longer than C. sanguinea. At immature stages, H. axyridis exhibited the highest survival percentage (49.2%), in comparison to the other coccinellids. For mean adult longevity, H. convergens was deficient, in comparison with the other species. Mean period of pre‑oviposition was the longest in C. sanguinea; the longest oviposition time occurred for H. axyridis; and the post‑oviposition period was similar between the coccinellids. Considering the reproductive parameters, H. axyridis showed the best performance in all aspects. For life table, the values of H. convergens were higher than, although close, to those of H. axyridis. Nevertheless, the high net reproductive rate of H. axyridis showed this species potential to increase population size. The biological characteristics of the exotic H. axyridis favors its invasion and establishment in Brazil, corroborating results noticed in other countries.